Effect of pandemic-induced PTSD in pregnant women on infant physical growth: a prospective cohort study - Fang Ye; Jie Chen; Xinying Gao; Hong Lin; Yuanmei Chen; Jing Liu; Qi Sun; Qi Zhang (BMC, 2024)
Abstract Background The COVID-19 pandemic has had a profound impact on global mental health, particularly affecting vulnerable groups such as pregnant women. Post-traumatic stress disorder (PTSD) in this population may potentially hinder infant physical development, underscoring the necessity for specific interventions. This study seeks to explore the prevalence of PTSD among pregnant women during the pandemic and its implications for infant physical development, thereby providing evidence to mitigate the adverse effects of the pandemic on maternal and child health. Methods A prospective cohort study was carried out involving 450 pregnant women from December 2022 to February 2023. Data included demographic details, PTSD evaluation using the PTSD Checklist-Civilian version (PCL-C) scale, coping mechanisms, and infant growth indicators at three months postpartum. Statistical methods included descriptive statistics, univariate analysis, and multivariate analysis of covariance (ANCOVA) to control for confounding factors. Results The study enrolled a total of 450 pregnant women. Following exclusions and follow-up attrition, 422 pregnant women were analyzed. There were 72 pregnant women with PTSD and 350 without PTSD. There was no statistically significant difference in birth weight between the two groups of participants. Three months after birth, infants of PTSD-positive mothers exhibited significantly lower weight percentiles at three months (P < 0.001), adjusted for birth weight, feeding method, and coping strategies. Multivariate analysis affirmed a 9.44-point reduction in weight percentile among infants in the PTSD-positive group (95% CI: 4.01-14.87, P = 0.001). Conclusion: Pregnant women suffering from PTSD during the pandemic are at risk of giving birth to infants with impaired physical growth. These findings highlight the critical need for mental health support for pregnant women to foster optimal infant development and to guide public health policies and clinical practices.